STRATEGI BINMAS POLSEK GUNUNGSITOLI ALO’OA DAN POLRES NIAS DALAM MENGHADAPI SOSIALISASI ADAPTASI KEBIASAAN BARU DITENGAH PANDEMI COVID-19 - ARIANUS HAREFA, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
In the current pandemic condition, the Indonesian National Police have a duty to maintain public security and order, namely; perform law enforcement functions; and provide protection, protection and services to the community in accordance with Article 13 of Law Number 2 of 2002 concerning the Indonesian National Police. To realize this task, the Chief of Police issued a Decree No. Mak / 2 / III / 2020 concerning Compliance with Government Policies in Handling Corona Virus. In carrying out their duties, the National Police in all areas of the Republic of Indonesia will take action against people who are still huddled together, hoarding basic necessities and other people's needs excessively and spreading hoax news. Then take action against various criminal acts caused by the pandemic such as theft, robbery, looting and other criminal acts, but the reality in the field is that there are still many criminal acts and that it seems that the community is not appropriate to these prohibitions, so that a problem arises, namely how is the role or strategy Binmas Polsek Gunungsitoli Alo'o and Polres Nias in Facing the Socialization of Adaptation of New Habits. To answer these problems, it is necessary to carry out a scientific study in the form of normative legal research, with a statutory approach and an analytical approach. Based on the results of the research, it shows that the role or strategy of the Gunungsitoli Alo'oa Police Department (Nias Police) in dealing with New Habit Adaptation (AKB) amid the Covid-19 Pandemic in the community is to carry out socialization activities through community education about the importance of understanding, awareness and understanding of the community about Adaptation. New habits in breaking the chain of covid-19 spread by following health protocols through implementing a clean lifestyle, namely; wash hands frequently, use masks, avoid crowds and always maintain a minimum distance of 1 (one) meter and maintain cleanliness and discipline yourself. Meanwhile, the efforts made by the Binmas Polsek Gunungsitoli Alo'oa (Nias Police) in dealing with New Habit Adaptation (AKB) amid the Covid-19 Pandemic in the community are carrying out activities that intensify the social appeal of Distancing and Physical Distancing, through patrol activities crowded places, both during the day and at night in order to maintain security and public order by checking the social security situation in villages in the jurisdiction of the Gunungsitoli Alo'oa Police, to appeal to the public to adhere to health protocols set by the government in order to accelerate the handling of the Corona Virus pandemic outbreak.